PENINGKATAN KINERJA KARYAWAN MELALUI KEPUASAN KERJA DAN KOMPENSASI SERTA LINGKUNGAN KERJA - wahyu setiaji; ken sudarti (JURNAL EKONOMI MANAJEMEN AKUNTANSI, 2012)
The purpose of this studyis to examine the effect compensation, work environment on job satisfaction and company performance. This study uses a population of employees of the Polytechnic Academy of Sciences Voyages Semarang by the number of 46 people, while the sample in this study were 46 employees. Sampling technique with census metode. methods of data analysis used was multiple regression.The results of this study is: The results of this study indicate that the performance of employees affected by the compensation and work environment. Job satisfaction is not as intervening variable between the effect of compensation and work environtmen. Job satisfaction is an intervening variabel between the influence of work environment on employee perormance. Hypotheses related to yield the result that compensation had an influence on job satisfaction, a regression toward the positive. Job satisfaction has an influence on the performance of human resources, with a positive regression coefficient. Work environment has a significant influence on employee performance, with positive direction. Keywords:       Compensation, Work Environment, Job Satisfaction, Employee Performance